Paradigms of programming languages and the difficulty of organizing the Algorithms and Data Structures course - Korotenko , Gregory; Korotenko , Leonid (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
The article considers the features of drawing up themeaningful material about the features of the implementation of software components (units) when implementing a number of algorithms within the “Algorithms and Data Structures” Course. It is shown that the number of implementations of the original algorithms significantly increases when using different programming languages. The number of possible implementations increases even more when using different paradigms, realized in the selected programming languages.